α-Synuclein BAC transgenic mice exhibit RBD-like behaviour and hyposmia: a prodromal Parkinson's disease model - Taguchi, Tomoyuki; Ikuno, Masashi; Hondo, Mari; Parajuli, Laxmi Kumar; Taguchi, Katsutoshi; Ueda, Jun; Sawamura, Masanori; Okuda, Shinya; Nakanishi, Etsuro; Hara, Junko; Uemura, Norihito; Hatanaka, Yusuke; et al. (Brain (London, England : 1878), 2020)
Parkinson's disease is one of the most common movement disorders and is characterized by dopaminergic cell loss and the accumulation of pathological α-synuclein, but its precise pathogenetic mechanisms remain elusive. To develop disease-modifying therapies for Parkinson's disease, an animal model that recapitulates the pathology and symptoms of the disease, especially in the prodromal stage, is indispensable. As subjects with α-synuclein gene (SNCA) multiplication as well as point mutations develop familial Parkinson's disease and a genome-wide association study in Parkinson's disease has identified SNCA as a risk gene for Parkinson's disease, the increased expression of α-synuclein is closely associated with the aetiology of Parkinson's disease. In this study we generated bacterial artificial chromosome transgenic mice harbouring SNCA and its gene expression regulatory regions in order to maintain the native expression pattern of α-synuclein. Furthermore, to enhance the pathological properties of α-synuclein, we inserted into SNCA an A53T mutation, two single-nucleotide polymorphisms identified in a genome-wide association study in Parkinson's disease and a Rep1 polymorphism, all of which are causal of familial Parkinson's disease or increase the risk of sporadic Parkinson's disease. These A53T SNCA bacterial artificial chromosome transgenic mice showed an expression pattern of human α-synuclein very similar to that of endogenous mouse α-synuclein. They expressed truncated, oligomeric and proteinase K-resistant phosphorylated forms of α-synuclein in the regions that are specifically affected in Parkinson's disease and/or dementia with Lewy bodies, including the olfactory bulb, cerebral cortex, striatum and substantia nigra. Surprisingly, these mice exhibited rapid eye movement (REM) sleep without atonia, which is a key feature of REM sleep behaviour disorder, at as early as 5 months of age. Consistent with this observation, the REM sleep-regulating neuronal populations in the lower brainstem, including the sublaterodorsal tegmental nucleus, nuclei in the ventromedial medullary reticular formation and the pedunculopontine nuclei, expressed phosphorylated α-synuclein. In addition, they also showed hyposmia at 9 months of age, which is consistent with the significant accumulation of phosphorylated α-synuclein in the olfactory bulb. The dopaminergic neurons in the substantia nigra pars compacta degenerated, and their number was decreased in an age-dependent manner by up to 17.1% at 18 months of age compared to wild-type, although the mice did not show any related locomotor dysfunction. In conclusion, we created a novel mouse model of prodromal Parkinson's disease that showed RBD-like behaviour and hyposmia without motor symptoms.